Entre Espanha e Portugal: a arte esquemática na Média e Baixa Bacia do Douro - Sanches, Maria de Jesus (2022)
This is an overview of the schematic rock art of the mid-lower Douro basin, covering the border region between Portugal and Spain (Trás-os-Montes and Beira Alta on the one hand, and Zamora and Salamanca on the other). An internal chronological framework is put forward for the schematic art, which takes into account the themes and their formalisms. Chronological and cultural period: from the Mesolithic to the Bronze Age.